2013
DOI: 10.1002/adom.201200020
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Bright Molecule‐Like State and Dark Intrinsic State in Green‐Fluorescence Graphene Quantum Dots via Ultrafast Spectroscopy

Abstract: Graphene quantum dots (GQDs) have recently emerged as a promising type of low‐toxicity, high‐biocompatibility, and chemically inert fluorescence probe with a high resistance to photobleaching. They are a prospective substitution for organic materials in light‐emitting devices (LED), enabling the predicted concept of much brighter and more robust carbon LED (CLED). However, the mechanism of GQD emission remains an open problem despite extensive studies conducted so far, which is becoming the greatest obstacle i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 153 publications
(76 citation statements)
references
References 36 publications
7
69
0
Order By: Relevance
“…Yang et al provided further evidence from transient spectra. A charge separation could exist between sp 2 cluster and defect states, leading to a defect state luminescence in a dominated role for green emission GQDs 20,21,25,26 . However, there is rare report on the synthesis of highly luminescent GQDs with tailoring color emissions like inorganic nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al provided further evidence from transient spectra. A charge separation could exist between sp 2 cluster and defect states, leading to a defect state luminescence in a dominated role for green emission GQDs 20,21,25,26 . However, there is rare report on the synthesis of highly luminescent GQDs with tailoring color emissions like inorganic nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Plausible reasons could be quantum confinement, size heterogeneity,a nd the participation of defect/trap states. [3][4][5][6] Recently,L ie and co-workersa ttributed the origin of green luminescence in CDs to special edge effects controlled by edge carbon atoms and C=Of unctional groups. [7] However, Peng et al observed size-dependent PL responses from fluorescent CDs are also reported.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrafast spectroscopy is a powerful tool for investigating the electronic structure, excitonic properties and carrier dynamics for various new types of fluorescent nanomaterials, for example, graphene oxide, 35,36 graphene quantum dots (QDs), 37 carbon nanodots, 38,39 polymer nanoparticles, 40 direct bandgap semiconductor QDs 41243 and Si NCs. 44249 In our previous work, we produced novel Si NCs with unprecedented ultrabright fluorescence and single-exponential decay.…”
Section: Introductionmentioning
confidence: 99%